Column leaching of ion adsorption rare earth ore at low ammonium concentration - Qiyuan Shi; Yu Zhao; Xiaoyu Meng; Li Shen; Guanzhou Qiu; Xigang Zhang; Hong Yu; Xiao He; Huajin He; Hongbo Zhao (Journal of Materials Research and Technology, 2022)
Ammonium sulfate ((NH4)2SO4) is currently the most commonly used leaching agent for the extraction of ion adsorption rare earth ore (IARE-ore) in industrial production. However, ammonium sulfate technology has been gradually restricted to use mainly due to its environmental damage, thus resulting in serious challenges in the IARE-ore industry. Based on the leaching mechanism of cation exchange, a high ammonium concentration is required in ammonium sulfate leaching. In addition, the anion of sulfate radicals has almost no ability to leach rare earth elements (REEs), which are also a component of environmental pollution. Therefore, it is important to reduce the concentration of the leaching agent, especially the ammonium concentration in the IARE-ore leaching process. In this work, ammonium citrate was used as a new leaching agent in IARE-ore leaching. The column leaching results showed that high REEs recovery can be obtained at relatively low ammonium concentration. Both of the cation and anion components of ammonium citrate were effective in the REEs leaching process, thus resulting in cooperative effects. A liquid/solid ratio of 4:1 and a pH of 6 were the appropriate conditions for the extraction of rare earth with ammonium citrate, while the appropriate pH for ammonium sulfate was 2. This work provides a new approach to solving the challenge of traditional ammonium technology by designing and changing the molecular structure of ammonium leaching agents.